Clinical Characteristics of Early-Onset and Late-Onset Multiple Sclerosis in Patients from Lithuania - Emilija Šlajūtė; Naglis Vičkačka; Tautvydas Klėgėris; Ingrida Ulozienė; Renata Balnytė (Medicina)
Background and Objectives: Early-onset MS (EOMS) and late-onset MS (LOMS) differ in terms of symptom presentation, disease progression, and disability outcomes. This study aims to evaluate the clinical characteristics of patients with EOMS and LOMS in Lithuania. Materials and Methods: A retrospective analysis of patients’ medical records was conducted at the Lithuanian University of Health Sciences, Kaunas Clinics Department of Neurology. This study included 97 patients with multiple sclerosis, of which 34 were diagnosed with EOMS and 63 with LOMS. Results: The female/male ratio did not differ significantly in the EOMS group (1.26:1), while in the LOMS group, the female-to-male ratio was 2:1. All EOMS patients were diagnosed with relapsing–remitting multiple sclerosis (RRMS), while in the LOMS group, RRMS was observed in 55.6%, secondary progressive multiple sclerosis (SPMS) was observed in 27%, and primary progressive multiple sclerosis (PPMS) was observed in 17.4% of patients (p < 0.001). The most common initial symptoms in the EOMS group were brainstem dysfunction (50%), and sensory (38.2%) and visual (26.5%) disorders, whereas LOMS patients predominantly experienced brainstem dysfunction (50.8%) and motor impairments (47.6%). The EOMS group experienced more clinical relapses in the first year after diagnosis, along with more frequent radiological signs of disease activity compared to LOMS (p < 0.001). Both groups demonstrated a significant increase in Expanded Disability Status Scale (EDSS) score at the last follow-up visit compared to the baseline, while the LOMS group had higher EDSS scores both at the baseline and at the last follow-up compared to the EOMS group (p < 0.001). Only LOMS patients had an increase in Multiple Sclerosis Severity Score (MSSS) at the last follow-up compared to the baseline (p = 0.028), and MSSS was higher than in EOMS patients both at the baseline (p = 0.004) and the last follow-up (p < 0.001). Conclusions: There was no significant gender difference in the EOMS group, whereas in the LOMS group, females were predominant. Both groups had RRMS as the most common disease course. At the onset of MS, brainstem dysfunction was the most common symptom in both patient groups. EOMS patients had a more active disease course, in contrast to LOMS patients, who exhibited higher levels of disability, suggesting a progressive disease.